Bone Marrow T-Cell Sequestration and Lymphopenia Accompanying Ischemic Stroke are Mediated by T-Cell S1P1 Loss. (1st September 2019) - Chongsathidkiet, Pakawat; Dechant, Cosette; Wilkinson, Daniel; Wang, Haichen; Kemeny, Hanna; Cui, Xiuyu; Lorrey, Selena; Laskowitz, Daniel T; Fecci, Peter E
Abstract: INTRODUCTION: Sequestration of T-cells in bone marrow is a phenomenon recently characterized by our group in the setting of intracranial tumors. Our findings suggest that it is the intracranial location rather than tumor histology that elicits this phenotype. Sequestration is accompanied by lymphopenia and lymphoid organ contraction and is mediated by loss of the S1P1 receptor from the T-cell surface. We now reveal that this phenomenon is not only unique to brain tumors, but accompanies additional intracranial pathologies, most notably ischemic stroke. METHODS: Blood, bone marrow, and spleens were collected from mice at day 2, 5, 7, or 14 following stroke via middle cerebral artery occlusion or sham surgery and analyzed by flow cytometry. T-cell S1P1 levels were assessed, along with T-cell counts in each compartment. S1P1 receptor stabilization was achieved with a knock-in model that inhibited receptor internalization. RESULTS: Following stroke induction, T-cells accumulated in the bone marrow of injured mice. T-cell numbers peaked at day 7 poststroke before returning to normal levels by day 14. Bone marrow accumulation was accompanied by transient T-cell lymphopenia and splenic contraction following stroke. T-cells in the bone marrow yielded decreased levels of S1P1 on their surface. Conversely, mice with genetically stabilized T-cell S1P1 were protected against sequestration, lymphopenia, and splenic contraction following stroke. CONCLUSION: Bone marrow T-cell sequestration occurs transiently following stroke and is mediated by the S1P-S1P1 axis. This may prove to be an adaptive mechanism to limit intracranial inflammation following an initial insult. Better understanding of this phenomenon may uncover a novel mechanism of immune privilege and allow for therapeutic modulation in the setting of stroke, brain tumor, and other types of intracranial injury.